A smooth tubercle bacillus from Ethiopia phylogenetically close to the Mycobacterium tuberculosis complex - Yenew, Bazezew; Ghodousi, Arash; Diriba, Getu; Tesfaye, Ephrem; Cabibbe, Andrea Maurizio; Amare, Misikir; Moga, Shewki; Alemu, Ayinalem; Dagne, Binyam; Sinshaw, Waganeh; Mollalign, Hilina; Meaza, Abyot; et al. (Nature communications, 2023)
The Mycobacterium tuberculosis complex (MTBC) includes several human- and animal-adapted pathogens. It is thought to have originated in East Africa from a recombinogenic Mycobacterium canettii -like ancestral pool. Here, we describe the discovery of a clinical tuberculosis strain isolated in Ethiopia that shares archetypal phenotypic and genomic features of M. canettii strains, but represents a phylogenetic branch much closer to the MTBC clade than to the M. canettii strains. Analysis of genomic traces of horizontal gene transfer in this isolate and previously identified M. canettii strains indicates a persistent albeit decreased recombinogenic lifestyle near the emergence of the MTBC. Our findings support that the MTBC emergence from its putative free-living M. canettii -like progenitor is evolutionarily very recent, and suggest the existence of a continuum of further extant derivatives from ancestral stages, close to the root of the MTBC, along the Great Rift Valley. The Mycobacterium tuberculosis complex (MTBC) includes several pathogens thought to have originated in East Africa from an ancestor closely related to Mycobacterium canettii . Here, the authors describe a clinical tuberculosis strain isolated in Ethiopia that has typical M. canettii features but is phylogenetically much closer to the MTBC clade, supporting that the emergence of MTBC pathogens is a recent evolutionary event.